The Top-Down Model: A Discussion of Corporate Social Responsibility Policy in China - Li, Shu; Appiah-Konadu , Paul (Journal of Sustainable Development Law and Policy, 2025)
Corporate Social Responsibility (CSR) has gained significant prominence in China in the period after the reforms and opening-up of the Chinese economy which ushered in the separation of corporate management and state administration as well as the integration of the Chinese economy with the global economy. Since then, the Chinese government and citizens have realized the need to hold enterprises responsible for the effects of their activities on society; and hence began to formulate CSR policies, and to integrate relevant laws, incentives, supervision and control mechanisms in corporate regulations. In 2001, China’s accession to the WTO provided a platform for international reference and exchanges for the development of CSR policies. In 2006, CSR was recognized by the country’s highest authority in legal form for the first time, which also meant that CSR became a national economic development strategy and policy. Unlike the private sectorled CSR in Europe and North America, this study shows that CSR in China is mainly a government-guided phenomenon and more popular among state-owned enterprises (SOE).In this light, we opine that the improvement of CSR policy and practice in China requires reforms designed with special consideration of the unique characteristics of the Chinese society to encourage stakeholder involvement in the policy formulation and participation in the implementation process.